Conhecendo o idoso na comunidade : sudsídios para a equipe e para os serviços de saúde, Guarapuava-PR - Pilger, Calíope (2010)
Elderly have characteristics that need to be addressed by health services. Researches that aim to study their health profile are fundamental for their assistance, for they provide health professionals and managers with information to design actions and public policies that assure care with effectiveness and quality. To analyze the health and socio-demographic profile of elderly living in the city of Guarapuava - PR. This is a transversal study with people with 60 years-old and older living in Guarapuava - PR, enrolled in 30 (thirty) city Health Centers. Out of the 5508 elderly enrolled 359 were chosen by proportional stratified sampling. Data was collected using sections I, II, III and IV of the BOAS questionnaire (Brazil Old Age Schedule) which were applied to the elderly in their homes by trained interviewers. Data was analyzed using the Statistic software and was presented using descriptive analysis (simple frequency and percentage, chi-square and Fisher's exact test for association). Outcomes: 64.3% interviewees were women and 35.7% men. The main diseases manifested by them were arterial hypertension (34.9%), diabetes (12.4%) and arthritis/arthrose (12.2%). Most elderly reported being satisfied about their lives (83.4%), their health self-perception, visual and auditory accuracy was good (54.9%, (45.1%) and (48.6%), respectively. 65.2% of elderly found their dental state poor, 6.8% found it horrible and 73.5% reported that most of their teeth are missing. There were low proportions of elderly hospitalization (9.0%), physical therapy appointments (4.5%) and urgency situations (11.8%) in the past three months. Regarding utilization of medical and dental services 70.4% and 26.4% went to public institutions respectively. Most interviewees showed satisfaction towards public health institutions (83.1%), private clinics and health maintenance organizations (92.2%). Women displayed higher mild dependence level (70.5%) and moderate/severe (62.3%) than men, as 75% of them did not present any functional disability. For the elders aged between 70-79, the chance of having moderate/severe dependence increases by six-fold, and up to eleven-fold for those aged 80 or more. Concerning marital status the widows presented better opportunity to have moderate/severe dependence, with 7.1 odds ratio. It was observed that professional formation is important but beyond that, getting to know the real needs of elders is a fundamental key to generate health indicators that cannot be obtained from other data sources and which are essential for planning actions by managers, politician leaders and health professionals.